NT-proBNP, Cardiometabolic Risk Factors, and Nutritional Status in Hemodialysis Patients. (17th September 2017) - Ducros, Jacques; Larifla, Laurent; Merault, Henri; Foucan, Lydia
Abstract : Background. We aimed to evaluate the association between NT-proBNP and malnutrition in HD patients while taking into account the four established categories of parameters for diagnosis of protein energy wasting (PEW). Methods . A cross-sectional study was performed in Afro-Caribbean dialysis patients. One component in each of the 4 categories for the wasting syndrome was retained: serum albumin ≤ 38 g/L, BMI ≤ 23 Kg/m 2, serum creatinine ≤ 818  µ mol/L, and normalized protein catabolic rate (nPCR) ≤ 0.8 g/kg/day. NT-proBNP was assessed using a chemiluminescence immunoassay. Two multivariate logistic regression models were performed to determine the parameters associated with high NT-proBNP concentrations. Results. In 207 HD patients, 16.9% had PEW (at least three components). LVEF lower than 60% was found in 13.8% of patients. NT-proBNP levels ranged from 125 to 33144 pg/mL. In model 1, high levels of NT-proBNP (≥6243 pg/mL) were independently associated with PEW OR 14.2 (3.25–62.4), male gender 2.80 (1.22–6.57), hsCRP > 5 mg/L 3.90 (1.77–8.57), and dialysis vintage > 3 years 3.84 (1.35–10.8). In model 2, LVEF OR was 0.93 (0.88–0.98). NT-proBNP concentrations were significantly higher when the PEW component number was higher. Conclusion. In dialysis patients, high NT-proBNP levels must draw attention to cardiac function but also to nutritional status.